ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF BUDGET MANAGEMENT OF BOS FUNDS AT SMA NEGERI 1 KERITANG - Rio Rahamadi; Muhammad Fauzan; Sri Hidayanti (Indragiri Research Center (ingreat), 2026)
This study aims to analyze the effectiveness and efficiency of School Operational Assistance (BOS) fund management at SMA Negeri 1 Keritang. The research employs a quantitative approach with an explanatory design using effectiveness and efficiency ratio analysis. The results indicate that the effectiveness level of BOS fund management during 2021–2024 is categorized as effective, with ratios ranging from 99.91% to 100%, reflecting a high level of conformity between budget planning and realization. However, the efficiency level is categorized as less efficient, with similar ratio values indicating a tendency to fully absorb the budget without significant cost-saving efforts. These findings suggest that while budget implementation is optimal, improvements in allocation planning and expenditure control are necessary to enhance efficiency.